Industrial-scale metal hydride hydrogen compressors developed at the South African Institute for Advanced Materials Chemistry. (2018) - Lototskyy, Mykhaylo; Klochko, Yevgeniy; Wafeeq Davids, Moegamat; Pickering, Lydia; Swanepoel, Dana; Louw, Gerhard; van der Westhuizen, Burt; Chidziva, Stanford; Sita, Cordellia; Bladergroen, Bernard; Linkov, Vladimir
Abstract: This work provides an overview of R&D activities at South African Institute for Advanced Materials Chemistry (SAIAMC) on metal hydride hydrogen compression technology with a focus on engineering solutions for industrial-scale applications. A summary of layout features, as well as test / operation results are presented for industrial-scale prototypes of: (i) 1-stage H2 compressor for refueling station (50–200 bar, up to 13 Nm 3 /h), and (ii) 3-stage H2 compressor (3–200 bar, up to 5 Nm 3 /h). The developed systems provide hydrogen compression utilizing low-grade steam (T=120–140 °C) and cooling water (T=15–25 °C) available at sites of industrial customers.